2014
DOI: 10.1159/000366377
|View full text |Cite
|
Sign up to set email alerts
|

MiR-206 Controls the Phenotypic Modulation of Pulmonary Arterial Smooth Muscle Cells Induced by Serum from Rats with Hepatopulmonary Syndrome by Regulating the Target Gene, Annexin A2

Abstract: Background: Hepatopulmonary syndrome (HPS) is a serious complication of advanced liver disease that is characterised by intrapulmonary vascular dilatation (IPVD) and arterial hypoxemia. Pulmonary vascular remodelling (PVR) is an important pathological feature of HPS, but the potential mechanisms underlying PVR remain undefined. Recent findings have established the essential role of changes in Annexin A2 (ANXA2) in controlling the phenotypic modulation of pulmonary artery smooth muscle cells (PASMCs) in PVR ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Numerous miRNAs and genes have been reported to be associated with the development of PAH [15,16,17,18]. In this study, we performed a case-control association study to identify the relationship between the rs2910164 polymorphism and risk of PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous miRNAs and genes have been reported to be associated with the development of PAH [15,16,17,18]. In this study, we performed a case-control association study to identify the relationship between the rs2910164 polymorphism and risk of PAH.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that PTEN localizes to the apical plasma membrane during epithelial morphogenesis to mediate the enrichment of PtdIns (4,5)P2 at this domain during cyst development in three dimensional culture. Then, AX2 binds PtdIns (4,5)P2 and thus is recruited to the apical surface, which in turn recruits Cdc42 to the apical plasma membrane, causing the organization of the sub-apical actin cytoskeleton and formation of the apical surface and lumen. 26 Therefore, we checked whether PTEN interacts with AX2 by using Immunoprecipitation assay.…”
Section: Pten Activates Cdc42 In Pmvecs Via Ax2mentioning
confidence: 99%
“…This suggested that the increased total PTEN was mainly p-PTEN. Interestingly, it has been shown that AX2 binds PtdIns (4,5)P2 and is recruited to the apical surface. 26 Our previous studies had reported that silencing AX2 expression inhibited cell migration and proliferation in the pathogenesis of HPS.…”
Section: Mcarolina Florian Has Reported That Elevated Activity Of CDmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, it has been estimated that more than one-third of mRNAs of human genes are regulated by human miRNAs [14]. Accumulative evidence demonstrates that miRNAs are critical for regulating the expression of oncogenes or tumor suppressor genes, which will result in tumorigenesis [15,16] as well as other medical disorders [17,18]. Saunders et al proposed that a single nucleotide change in the "seed sequence" of a target site may affect miRNA binding to target sites in the 3′UTR of human genes [19].…”
Section: Introductionmentioning
confidence: 99%